Characterization of a preleukemic state induced by Moloney murine leukemia virus: evidence for two infection events during leukemogenesis. - Davis, B R (1987)
A preleukemic state in mice inoculated with Moloney murine leukemia virus (Mo-MuLV) was characterized. Six to 10 weeks after neonatal inoculation, animals developed mild splenomegaly and generalized hematopoietic hyperplasia. The hyperplasia was evident from myeloid and erythroid progenitor assays. A nonleukemogenic variant, Mo+PyF101 Mo-MuLV, did not induce the hyperplasia; this suggests that the hyperplasia is a necessary event in Mo-MuLV leukemogenesis. Another variant, MF-MuLV, which contains the long terminal repeat of Friend MuLV and causes erythroid leukemia instead of T-cell lymphoma, also induced the preleukemic hyperplasia. A model for Mo-MuLV leukemogenesis is presented in which two infection events are necessary: the first leads to generalized hematopoietic hyperplasia, and the second results in site-specific insertion and long terminal repeat activation of cellular protooncogenes.